(untitled) (Third Sector Social Economic Review, 2023)
In this study, the presence of Syrians under Temporary Protection (SuTP) in Turkey is evaluated on the axis and the place and contributions of the SuTP population in the economy are examined. Although there are different approaches regarding the SuTP population, the focus of this study is on the economic contributions of the SuTP. Turkish Citizens and Syrian households, firms and labor accounts are separated within the framework of the Macro Social Accounting Matrix (SAM) in order to evaluate the SuTP population in a holistic structure in the Turkish economy. An external shock was given to the economy by performing income multiplier analysis with the obtained Macro-SAM and the effects of external income shock on production activities, demand for goods, households and firms were evaluated within the framework of Turkish Citizens and Syrian distinction. According to the results of the analysis in which three different scenarios were tested, it was calculated that the SuTP population could not benefit enough from the increase in economic welfare, the support given to the SuTP households also increased the income of the Turkish Citizens households, on the other hand, if the SuTP workforce was supported, the Turkish Citizens and SuTP population could gain more benefits. It has been seen that the SuTP population can provide more benefits to the Turkish economy if the applied supports are directed to labor force and production activities instead of households.